2017
DOI: 10.1111/jog.13239
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D and risk of preterm birth: Up‐to‐date meta‐analysis of randomized controlled trials and observational studies

Abstract: Aim: We performed a meta-analysis of randomized controlled trials (RCT) and observational studies to answer the two following questions: (i) whether low maternal circulating 25 hydroxyvitamin D (25-OHD) is associated with an increased risk of preterm birth (PTB) or spontaneous PTB (sPTB); and (ii) whether vitamin D supplementation alone during pregnancy can reduce the risk of PTB. Methods: Literature search was carried out using Pubmed, Web of Science and Embase databases up to June 2016. Pooled OR or relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 43 publications
2
101
2
6
Order By: Relevance
“…These findings support the inverse association between maternal 25(OH)D and PTB risk found in the Hollis and Wagner et al randomized clinical trials [12,14,15] as well as epidemiological studies [410]. Wagner et al found a 59% lower risk of PTB for women with serum 25(OH)D concentrations ≥40 ng/mL compared to those with concentrations ≤20 ng/mL (p = 0.02) [12].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…These findings support the inverse association between maternal 25(OH)D and PTB risk found in the Hollis and Wagner et al randomized clinical trials [12,14,15] as well as epidemiological studies [410]. Wagner et al found a 59% lower risk of PTB for women with serum 25(OH)D concentrations ≥40 ng/mL compared to those with concentrations ≤20 ng/mL (p = 0.02) [12].…”
Section: Discussionsupporting
confidence: 73%
“…A 70% lower risk of PTB was found for women ≥20 ng/mL vs. <20 ng/mL in a study by Perez-Ferre et al (p = 0.002) [5]. Two recent meta-analyses also found that higher 25(OH)D concentrations significantly decreased the risk of PTB [9,10]. Post-hoc analysis of the Hollis and Wagner et al trials [12] and the Bodnar et al study [4] assessed the non-linear relationship between 25(OH)D and PTB, both identifying a decreasing risk of PTB as 25(OH)D increased to approximately 40 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Данные мета-анализов указывают на связь низких уровней 25(ОН)D во время беременности с повышен-ным риском преждевременных родов, который сни-жается при приеме препаратов витамина D [73], ге-стационного сахарного диабета [74], бактериального вагиноза, а также с низкой массой плода для данного гестационного возраста и более низкой массой ребен-ка при рождении [75,76]. При обследовании 800 бере-менных женщин, проживающих в г. Санкт-Петербург и Ленинградской области, недостаточность и дефицит витамина D встречался у 100% женщин с бесплодием, у пациенток с невынашиванием беременности дефи-цит и недостаточность витамина D наблюдался в 6 раз чаще, у беременных с преэклампсией в 5 раз чаще на-блюдался низкий уровень витамина D; при физиологи-ческой протекающей беременности недостаточность витамина D выявлена лишь у 18,5% женщин, дефицит витамина D выявлен не был [77].Результаты опубли-кованного недавно первого РКИ, в котором исследо-валось влияние приема витамина D во время бере-менности на массу костной ткани ребенка (MAVIDOS) показали, что при приеме 1000 МЕ колекальциферола во время беременности в целом не наблюдалось уве-личение массы костной ткани в сравнении с плацебо, но у родившихся в зимнее время детей было отмечено увеличение МПК почти на 10%; была также показана эффективность и безопасность приема 1000 МЕ коле-кальциферола для восполнения дефицита витамина D у беременных женщин [78].…”
Section: витамин D и репродуктивная функцияunclassified
“…[9][10][11][12] The relationship of vitamin D and inflammation resembles hen and egg conundrum, whether inflammation reduces vitamin D concentration or vitamin D dampens inflammation still remains a puzzle. [21][22][23] Therefore, aforementioned observations instigated us to study if any alterations in vitamin D-mediated signals originating from fetal side modulate the maternal immune system in triggering the premature activation of labor as the information till date is fragmented and inconclusive, thus bestowing a major gap between two pathways. [13][14][15][16][17] In cancer and other immunological disorders, vitamin D has been extensively known to inhibit the expression and function of central transcription factor NF-κB.…”
mentioning
confidence: 99%